TiO2/graphene oxide immobilized in P(VDF-TrFE) electrospun membranes with enhanced visible-light-induced photocatalytic performance - Almeida, Nuno A.; Martins, Pedro M.; Teixeira, Sara; Lopes Da Silva, Jose A.; Sencadas, Vitor; Kuehn, K.; Cuniberti, Gianaurelio (Giovanni); Lanceros-Mendez, Senentxu; Marques, Paula A. A. P. (Journal of Materials Science, 2016)
Here, we report on the electrospinning of poly(vinylidene difluoride-co-trifluoroethylene) (P(VDF-TrFE)) copolymer fibrous membranes decorated with titanium dioxide/graphene oxide (TiO2/GO). The presence of the TiO2/GO increases the photocatalytic efficiency of the nanocomposite membrane towards the degradation of methylene blue (MB) when compared with the membranes prepared with naked TiO2, in UV and particularly in the visible range. Even a low content (3 %, w/w) of TiO2/GO in the fibers yields excellent photocatalytic performance by degrading 100 % of a MB solution after 90 min of visible light exposure. This may be attributed to a rapid electron transport and the delayed recombination of electron–hole pairs due to improved ionic interaction between titanium and carbon combined with the advantageous electric properties of the polymer, such as high polarization and dielectric constant combined with low dielectric loss. Thus, a promising system to degrade organic pollutants in aqueous or gaseous systems under visible light irradiation has been developed.
CRIS-Team Scopus Importer:2023-03-20